Effect of levosimendan injection on oxidative stress of rat myocardium - BASEL, Halil; Kavak, Servet; Demir, Halit; Meral, Ismail; Ekim, Hasan; MERAL, İSMAİL; Bektaş, Hava (My University, 2013)
This experiment was designed to investigate the effect of levosimendan injection on lipid peroxidation product malondialdehyde (MDA) and antioxidant glutathione (GSH) levels, and activities of antioxidant enzymes in myocardium of rats. Twenty male Wistar-albino rats were divided randomly into 2 study groups, each consisting of 10 rats. The animals in the first group were not treated with drug and served as control. It was found that the MDA and GSH levels decreased in levosimendan injected group. Superoxide dismutase, glutathione peroxidase, catalase and carbonic anhydrase enzyme activities were lower in levosimendan injected group than controls. It was concluded that lower tissue free radical level caused by levosimendan injection led to a lower antioxidant enzymes synthesis in the body and a decrease in the antioxidant enzyme activity and free radical scavenger level in myocardium of rat.